Modeling of Zinc Dynamics in the Synaptic Cleft: Implications for Cadherin Mediated Adhesion and Synaptic Plasticity - Wolf, Christoph; Weth, Agnes; Walcher, Sebastian; Lax, Christian; Baumgartner, Werner (Frontiers in Molecular Neuroscience, 2018)
While the numerous influences of synaptically released zinc on synaptic efficiency during long-term potentiation have been discussed by many authors already, we focused on the possible effect of zinc on cadherins and therefore its contribution to morphological changes in the context of synaptic plasticity. The difficulty with gaining insights into the dynamics of zinc-cadherin interaction is the inability to directly observe it on a suitable timescale. Therefore our approach was to establish an analytical model of the zinc diffusion dynamics in the synaptic cleft and experimentally validate, if the theoretical concentrations at the periphery of the synaptic cleft are sufficient to significantly modulate cadherin-mediated adhesion. Our results emphasize, that synaptically released zinc might have a strong accelerating effect on the morphological changes involved in long-term synaptic plasticity. The approach presented here might also prove useful for investigations on other synaptically released trace metals.